Perancangan Media Informasi Mengenai Kesadaran dalam Berlalu Lintas kepada Remaja di Kota Pariaman - Muhammad Rachmadani; Ahmad Akmal (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This design project aims to create an information media that can increase traffic awareness among adolescents in Pariaman City, considering the high number of traffic violations and accidents involving the teenage age group. The main medium produced is an animated motion graphic video, supported by complementary media such as posters, logos, X-banners, and campaign merchandise. The theoretical framework is based on visual communication design theory, information media, motion graphics, adolescent psychology, and an understanding of Law Number 22 of 2009 concerning Road Traffic and Transportation. The creation method uses a qualitative descriptive approach with data collection techniques including field observations, interviews with the Traffic Unit of the Pariaman Police Department, and questionnaires distributed to adolescents as the target audience. The creative process is carried out through pre-production, production, and post-production stages, applying verbal and visual strategies adapted to the characteristics of adolescents. The results show that motion graphic–based visual media using a flat vector style and a minimalist modern approach is effective in delivering traffic safety messages in an informative, engaging, and easily understood manner. The supporting media further strengthen the campaign message and expand communication reach, which is expected to foster greater traffic awareness and more responsible traffic behavior among adolescents.